Analiza pozycji ustrojowej kierownika budowy - Wiklański, Bartłomiej (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
This study deals with the issue of the position of the construction manager in the current legal order and it contains an indication of the effects of the proposed changes under the "Polish Deal". The discussed change is a postulate to limit the role of the construction manager in the construction of houses up to 70 square meters. For this purpose, the study has been divided into six subsections. The introduction to the discussed topic presents the position of the construction manager in the legal order. Next, a polemic is conducted with the thesis presented in the introduction. The study ends with a summary containing an answer to the problems raised in the article.

Niniejsze opracowanie dotyczy problematyki funkcjonowania kierownika budowy w obecnym porządku prawnym oraz wskazanie efektów postulowanych zmian w ramach „Polskiego Ładu”. Omawianą zmianą jest postulat ograniczenia roli kierownika budowy przy budowie domów do 70 m2. W tym celu został dokonany podział artykułu na sześć podpunktów. Wprowadzenie do omawianej tematyki przedstawia pozycję w porządku prawnym sylwetkę kierownika budowy oraz rozwiniecie uprawnień w porównaniu z postulatami „Polskiego ładu”. Kolejno zostaje przeprowadzona polemika z przedstawioną we wstępie tezą i antytezą. Całość zaś kończy podsumowanie zawierające odpowiedź na poruszone w artykule problemy.
An analysis of the constitutional position of the construction manager
Keywords: Construction law; construction manager; construction supervision; Prawo budowlane; kierownik budowy; nadzór budowlany